E-271 The brachioradial artery, a make-or-break variant for transradial approach endovascular interventions. (23rd July 2022) - Mirshahi, S; Sukumaran, M; Kappel, A; Lai, P; Frerichs, K; Aziz-Sultan, M; Patel, N; Du, R
Abstract : Introduction/Purpose: The brachioradial artery, or high origin of the radial artery, is defined as an origin of the radial artery proximal to the cubital fossa. This congenital anatomic variant is estimated to be present in as high as 10% of the population. At our institution, transradial access has become the preferred approach of performing diagnostic cerebral angiograms, and has also been utilized for neurointerventions in select patients. The purpose of this work is to describe this variant anatomy to the Neurointerventionalist, and suggest techniques to avoid or navigate this unique challenge. Methods: A retrospective cohort of 72 patients who underwent transradial artery approach neurointerventions at our institution from January 2018 to March 2021 was reviewed. Patients with the brachioradial artery variant were identified. Results: At our institution, this variant anatomy was identified in 4 of 72 radial neurointervention cases (5.6%), leading to access site conversion or case termination. The average diameter of the radial artery in these patients was 1.9 mm +/- 0.1 mm, and the ostium of the vessel was 1.5 mm +/- 0.1 mm. Access site conversion to the contralateral radial artery was performed in two of these patients; this variant was bilateral in one of these patients, and unilateral in the other. Conclusion: In our experience, the brachioradial artery variant has presented a significant challenge specific to neuroendovascular procedures requiring larger caliber (6 French or greater) co-axial sheaths and catheters. Disclosures: S. Mirshahi: None. M. Sukumaran: None. A. Kappel: None. P. Lai: None. K. Frerichs: None. M. Aziz-Sultan: 2; C; Proctor - Medtronic, Proctor - Microvention. N. Patel: None. R. Du: None.